Radar Cross Section Analysis of Unmanned Combat Aerial Vehicle (UCAV) using FEKO Software - J P Sijabat; T Indriyanto (AVIA, 2020)
Radar technology development encourages each country to develop military aircraft with small Radar Cross Section (RCS) size to bring out stealth behaviour, so that it is not easily detected by the enemy. In designing an airplane, computational methods become one of the best solutions in simulating the behaviour of an aircraft geometry when illuminated by electromagnetic waves. On this study, a calculation simulation of the RCS value was performed using FEKO (FElding bei Körn mit beliebiger Oberfläche) EM Simulation software for unmanned combat aerial vehicles (UCAV). Simulations are carried out in various conditions to find out factors affecting RCS value. These factors were analysed by varying radar frequency, material coating the plane, and methods of computational calculation. The results show that the greater the frequency, the greater the computational resources required as on higher number of mesh, more time needed to run the simulation, and required memory. However, the frequency is not directly proportional to the RCS value of the object. Methods of Momentum (MoM) and Multilevel Fast Multipole Method (MLFMM) perform computation calculations that are more detailed and more accurate comparedto Physical Optic (PO) full-ray tracing